THE INFLUENCE OF SERVICE QUALITY AND PERCEPTION OF BENEFITS ON GO-PAY SERVICE USER SATISFACTION - Mas Ning Zahroh (Asosiasi Dosen Muda Indonesia, 2022)
One of the electronic payment instruments is known as electronic money (emoney). E-money is a form of digital money. E-money functions to transfer the money balance data contained in our e-money to a computer or sales information system, so that the goods we want are purchased without spending additional cash. The purpose of this study was to determine the effect of service quality and perceived benefits partially and simultaneously on Go-Pay service user satisfaction. In this study, the method used is primary data, namely data taken from distributing questionnaires to Gundarma University students majoring in management class of 2017 who use Go-Pay services. The analytical tools used are Likert scale, validity test, reliability test, classic assumption test, determination, RLB, t test, and f test. From the results of the analysis tested, it can be concluded that service quality (X1) has no partial effect on user satisfaction of Go-Pay services, while the perceived benefits variable (X2) has a partial effect on user satisfaction of Go-Pay services. Service quality and perceived benefits simultaneously influence Go-Pay service user satisfaction. This confirms that perceived benefits have a positive influence on Go-Pay service user satisfaction.